Readability and Comprehension of Printed Patient Education Materials - Szabó, Pálma; Bíró, Éva; Kósa, Karolina (Frontiers in Public Health, 2021)
Background: Health literacy, a recently determined construct plays an important role in how individuals are able to manage their health. A useful approach for the assessment of health literacy is to measure the comprehension of available patient education materials (PEMs). Objective: We aimed at assessing the usefulness of PEMs available in Hungarian by testing comprehension of selected PEMs in different groups of users. Methods: Comprehension of patient education materials in the domain of healthcare was tested by selecting PEMs and creating questions based on their text in 3 dimensions of health literacy: understand, process/appraise, apply/use. 20 questions were created that could be answered without pre-existing knowledge by reading the appropriate text taken from PEMs. Comprehension was examined in four groups: laypersons, nonprofessional healthcare workers, 1st year healthcare students, and 5th year medical students. Readability indices were calculated for the same texts to which questions were created. Results: Laypersons answered less than 50% of the PEMs-based questions correctly. Nonprofessional healthcare workers performed better with 57% of right answers but significantly worse than healthcare students or medical students. Those with at least high school qualification (maturity exam) showed significantly higher comprehension compared to those with lower educational attainment. Persons in good or very good health also had significantly better comprehension than those in less favorable health. All readability indices showed that comprehension of the tested PEMs required at least ten years of schooling or more. Therefore, these PEMS are difficult to understand for persons with less than high school level of education. Conclusion: Rephrasing of the investigated patient educational materials would be recommended so that they better fit the educational attainment of the Hungarian population. Evaluation of the readability and comprehensibility of other PEMs also seems warranted.